PENGENALAN PERMAINAN TRADISIONAL SEJAK DINI SEBAGAI PEMBENTUKAN KARAKTER ANAK DI RUMAH BELAJAR DAN BERMAIN UNTUKMU SI KECIL JEMBER - Ana Aniati (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2013)
Education through traditional games, in addition to training children to have solidarity, social sensitivity, solidarity harmonious with the surrounding environment, is also one of the efforts to preserve the local wisdom education. Foundation "For you Little", the children of the lower classes are directed through positive education, such as: art, reading, writing, and discussion. USK also maintain and develop the traditional game to preserve the cultural heritage that is loaded this noble message. Sports and traditional games were preserved and developed, among others Gobag Sodor, hopscotch, jacks, Dakon, stilts, Jamuran, Jumpritan, and so forth. Education through traditional games, in addition to training children to have solidarity, social sensitivity, solidarity harmonious with the surrounding environment, is also one of the efforts to preserve the local wisdom education. The pattern of education through play groups have been arguing, inter alia, the low level of understanding of the community at that time about the importance of education outside of school quality, so hopefully with the education of children from an early age that began with vocational education and the arts, will arise the spirit love the culture of the nation and loved the country.